Analisis Kebijakan Perda No.7 Tahun 2013 Tentang Perlindungan Anak dan Perempuan Dalam Menangani Kasus Kekerasan Di Kota Serang - Maresky, Jeky Aprilian; Bangsawan, Try Adhi; Wajir, Dede Qodrat Al (Gapenas Publisher, 2025)
This study aims to analyze the implementation of the Regional Regulation (Perda) of Serang City Number 07 of 2013 concerning the Protection of Children and Women in handling cases of violence. The focus of the study is directed at the extent to which the policy is able to provide protection, services, and recovery for victims, as well as identify supporting and inhibiting factors in the field. This research was also carried out with a qualitative approach, where data was obtained through in-depth interviews, field observations, and analysis of official documents. The informants in the study included elements of the government, institutions engaged in the protection of women and children, law enforcement officials, and individuals who were victims of violence. The results of the study show that normatively, Regional Regulation No. 07 of 2013 has provided a firm legal basis in encouraging prevention, countermeasures, and recovery efforts for victims of violence. However, at the implementation level, there are still a number of obstacles such as lack of policy socialization, limited human resources, suboptimal support facilities, and coordination between agencies that have not been maximized. However, there are also supporting factors such as the commitment of the local government and the support of community organizations that care about the issue of protecting women and children. Therefore, the success of the implementation of Regional Regulation No. 07 of 2013 is determined by solid cooperation between the government, law enforcement officials, and community participation. This research is expected to be an input for policy makers to strengthen legal protection mechanisms, improve integrated services for victims, and encourage continuous evaluation of protection policies for children and women in Serang City